CCP4i2: the new graphical user interface to the CCP4 program suite. Issue 2 (4th February 2018) - Potterton, Liz; Agirre, Jon; Ballard, Charles; Cowtan, Kevin; Dodson, Eleanor; Evans, Phil R.; Jenkins, Huw T.; Keegan, Ronan; Krissinel, Eugene; Stevenson, Kyle; Lebedev, Andrey; McNicholas, Stuart J.; et al.
Abstract : CCP 4 i 2 is a graphical user interface to the CCP 4 (Collaborative Computational Project, Number 4) software suite and a Python language framework for software automation. Abstract : The CCP 4 (Collaborative Computational Project, Number 4) software suite for macromolecular structure determination by X‐ray crystallography groups brings together many programs and libraries that, by means of well established conventions, interoperate effectively without adhering to strict design guidelines. Because of this inherent flexibility, users are often presented with diverse, even divergent, choices for solving every type of problem. Recently, CCP4 introduced CCP 4 i 2, a modern graphical interface designed to help structural biologists to navigate the process of structure determination, with an emphasis on pipelining and the streamlined presentation of results. In addition, CCP 4 i 2 provides a framework for writing structure‐solution scripts that can be built up incrementally to create increasingly automatic procedures.